Influence of electrical impedance and mechanical bistability on Galfenol-based unimorph harvesters. (February 2017) - Deng, Zhangxian; Dapino, Marcelo J
A study on iron-gallium (Galfenol) unimorph harvesters is presented which is focused on extending the power density and frequency bandwidth of these devices. A thickness ratio of 2 (ratio of substrate to Galfenol thickness) has been shown to achieve maximum power density under base excitation, but the effect of electrical load capacitance on performance has not been investigated. This article experimentally analyzes the influence of capacitive electrical loads and extends the excitation type to tip impulse. For resistive-capacitive electrical loads, the maximum energy conversion efficiency achieved under impulsive excitation is 5.93%, while the maximum output power and output power density observed for a 139.5 Hz, 3m / s 2 amplitude sinusoidal base excitation is 0.45 W and 6.88mW / c m 3, respectively, which are 8% higher than those measured under purely resistive loads. A finite element model for Galfenol unimorph harvesters, which incorporates magnetic, mechanical, and electrical dynamics, is developed and validated using impulsive responses. A buckled unimorph beam is experimentally investigated. The proposed bistable system is shown to extend the harvester's frequency bandwidth.